2014
DOI: 10.5688/ajpe7810189
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Abbreviated Lecture with Interactive Mini-cases vs Traditional Lecture on Student Performance in the Large Classroom

Abstract: Objective. To compare the impact of 2 different teaching and learning methods on student mastery of learning objectives in a pharmacotherapy module in the large classroom setting. Design. Two teaching and learning methods were implemented and compared in a required pharmacotherapy module for 2 years. The first year, multiple interactive mini-cases with inclass individual assessment and an abbreviated lecture were used to teach osteoarthritis; a traditional lecture with 1 inclass case discussion was used to tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Another reason for re-evaluation of content delivery was expanding class size. After reviewing the literature on large classroom instruction and successes in converting lecture to small group format, 18,[32][33][34] we felt the need for consistency in topic delivery would be served well by dividing the very large class into two sections. The restructured self-care course remained a required 3-credit course in the third-year (PY3) year of the curriculum and intended to prepare students to handle routine questions in clinical practice experiences and future practice.…”
Section: Designmentioning
confidence: 99%
“…Another reason for re-evaluation of content delivery was expanding class size. After reviewing the literature on large classroom instruction and successes in converting lecture to small group format, 18,[32][33][34] we felt the need for consistency in topic delivery would be served well by dividing the very large class into two sections. The restructured self-care course remained a required 3-credit course in the third-year (PY3) year of the curriculum and intended to prepare students to handle routine questions in clinical practice experiences and future practice.…”
Section: Designmentioning
confidence: 99%
“…The results showed that after each proposal, the group using the online mode obtained better performance in an evaluation containing 20 items in the theme of pharmacotherapy [10].…”
Section: Discussionmentioning
confidence: 80%
“…Dialogic lectures, besides promoting the exchange of information between educators and students, represent the first step to facilitate the assimilation of knowledge and to convey the reality of the student towards meaningful content [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature in recent years has guided educators away from a traditional didactic lecture method and into the use of more innovative approaches to present complicated content. 14,[16][17][18][20][21][22][23][24][25][26][27][28][29][30] The ability to transition from rote memorization to application in the clinical setting can be enhanced by faculty modeling and increased student engagement. In redesigning the dyslipidemia module, the authors attempted to demonstrate how the didactic content could be applied in multiple situations that the students will encounter in the course of their careers, specifically: interactions with other health care professionals (panel discussion in PP466); determining appropriate treatment for a specific patient (Hour 4 of PP466 and Part 1 of PP468); evaluating literature for application to a patient case (Hour 3 of PP466 and Part 1 of PP468); reporting adverse events to appropriate entities (Part 2 of PP468); and working in teams to develop a drug therapy plan (Hour 4 of PP466 and all of PP468).…”
Section: Resultsmentioning
confidence: 99%